2017
DOI: 10.1007/978-3-319-69926-4_23
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study on Applying a Scrum Development Process for Safety-Critical Systems

Abstract: Abstract. Background: Agile techniques recently have received attention from the developers of safety-critical systems. However, a lack of empirical knowledge of performing safety assurance techniques, especially safety analysis in a real agile project hampers further steps. Aims: In this article, we aim at (1) understanding and optimizing the S-Scrum development process, a Scrum extension with the integration of a systems theory based safety analysis technique, STPA (System-Theoretic Process Analysis), for sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…Managing iterative changes (Beznosov 2003;Beznosov and Kruchten 2004;Jonsson et al 2012;Notander et al 2013a; Van Schooenderwoert and Shoemaker 2018) 2. Iterative validation of the software (Kasauli et al 2018;Paige et al 2008;Wang et al 2017;Wang and Wagner 2018) • Conduct the safety analysis iteratively, but validate the software incrementally (Kasauli et al 2018 (Jonsson et al 2012) 3. Heavy iterative testing of the software increments (Kasauli et al 2018;Rottier and Rodrigues 2008) • Use longer iterations to include testing and validation (Rasmussen et al 2009;Rottier and Rodrigues 2008) • Use automated, risk-based, continuous testing (Kasauli et al 2018)…”
Section: Area Of Concernmentioning
confidence: 99%
See 1 more Smart Citation
“…Managing iterative changes (Beznosov 2003;Beznosov and Kruchten 2004;Jonsson et al 2012;Notander et al 2013a; Van Schooenderwoert and Shoemaker 2018) 2. Iterative validation of the software (Kasauli et al 2018;Paige et al 2008;Wang et al 2017;Wang and Wagner 2018) • Conduct the safety analysis iteratively, but validate the software incrementally (Kasauli et al 2018 (Jonsson et al 2012) 3. Heavy iterative testing of the software increments (Kasauli et al 2018;Rottier and Rodrigues 2008) • Use longer iterations to include testing and validation (Rasmussen et al 2009;Rottier and Rodrigues 2008) • Use automated, risk-based, continuous testing (Kasauli et al 2018)…”
Section: Area Of Concernmentioning
confidence: 99%
“…Notander et al (2013a) and Van Schooenderwoert and Shoemaker (2018) suggested an iterative framework for safety-critical software development in which documentation is also treated iteratively and incrementally. Wang et al (2017) and Wang and Wagner (2018) stated how traditional safety analysis and verification techniques are difficult to use with agile software development. Wang et al (2017) proposed a process called S-Scrum, which uses a hazard analysis technique called System-Theoretic Process Analysis (STPA) and allows for an iterative validation, and Wang and Wagner (2018) proposed using a combination of STPA and Behavior-Driven Development (BDD).…”
Section: Life Cyclementioning
confidence: 99%
“…Create software development plan [KKK14] based on features [RHJS09] at the planning meeting [SHMH14], [HHS + 16]. Document chosen modelling approach, implementation language, development environment and assessment tools [DK16] and determine safety requirements [WRW17]. Combine sprint planning with retrospective [SM16b], [RHJS09], [McM16] to empirically improve estimations [FSOO13].…”
Section: Planning Meetings and Retrospectivesmentioning
confidence: 99%
“…In 2016, we proposed to use STPA in a Scrum development process [5]. It showed a good capability to ensure agility and safety in a student project [12]. However, we verified the safety requirements only at the end of each sprint by executing UAT together with TDD in development.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, a BDD test scenario should test if the ultrasonic sensor provides the feedback that the forward distance <= threshold (means there is an 2 Since we focus on safety in our research, we assign a safety analyst as the QA role in our context. 3 More descriptions of STPA for safety analysis are given in [7] concerning an example of using STPA in an airbag system and [12] concerning the use of STPA in a Scrum development process. 4 We illustrate a BDD test scenario using only three basic steps "Given" "When" "Then".…”
Section: Stpa Integrated Bdd For Safety Analysis Andmentioning
confidence: 99%